Identification of genera of tubificid worms in Bangladesh through morphological study - Mariom, -; Liza, Sharmin Nahar; Mollah, Md Fazlul Awal (Asian Journal of Medical and Biological Research, 2016)
<!–[if gte mso 9]> ismail - [2010] 11.5606 <![endif]–> Tubificids are aquatic oligochaete worms (F- Naididae, O- Haplotaxida, P- Annelida) distributed all over the world. The worms are very important as they are used as live food for fish and other aquatic invertebrates. A step was taken to identify the genera of tubicifid worms that exist in Mymensingh district, Bangladesh on the basis of some external features including the shape of their anterior (prostomium) and posterior end, number of body segment and arrangement of setae. The study result indicated the existence of three genera among the tubificid worms. These were Tubifex, Limnodrilus and Aulodrilus. All these three genera possessed a cylindrical body with a bilateral symmetry formed by a series of metameres. The number of body segments ranged from 34 to 120 in Tubifex, 50 to 87 in Limnodrilus, and 35 to 100 in Aulodrilus. In Tubifex, the first segment, with the prostomium, was round or triangular bearing appendages, whereas, in Limnodrilus and Aulodrilus, the prostomium without appendages was triangular and conical, respectively. Three types of setae i.e., hair setae, pectinate setae and bifid setae of various sizes were found in Tubifex, whereas, Limnodrilus possessed pectinate setae and bifid setae of more or less similar size and shape; and Aulodrilus possessed only hair setae and bifid setae of different size. Asian J. Med. Biol. Res. March 2016, 2(1): 27-32 <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>